Optimal nozzle exit position for a single-phase ejector (Experimental, numerical and thermodynamic modelling). (December 2022) - Rand, Charles P.; Croquer, Sergio; Poirier, Michel; Poncet, Sébastien
Highlights: A single-phase supersonic ejector working with R245fa is considered. The experiments indicate three maxima of the entrainment ratio for variable NXP. RANS model accurately predicts the relation between the entrainment ratio and NXP. Improved thermodynamic model should include NXP for better prediction performance. The compound choking criterion explains the displacement of the choking location. Abstract: Many authors have explored the performance of single-phase ejectors. A significant number of studies have focused on the impact of the nozzle head exit position (NXP) on the ejector performance and reported the existence of a single optimal NXP. However, few others found multiple optimal NXP for the same set of operating conditions. Using an experimental test bench and numerical simulations, the current study observes peaks and valleys in the entrainment ratio ( ω ) curve when the NXP varies for fixed operating conditions. The Reynolds-Averaged Navier Stokes (RANS) model has successfully captured the complex flow behavior associated with the change in NXP. The Mach contours and compound choking criterion ( β ) inside the ejector are used to investigate how the NXP affects the entrainment ratio. The results suggest that, the more a flow is double-choked and comprised of a longer compound supersonic section, the more the NXP is deemed optimal. Moreover, the compound supersonic section length is found to vary significantly with the change in NXP. This is the first study to utilize the compound choking theory to explain the impact of the NXP. The compound choking criterion ( β ) can be used to identify optimal NXP in a commercial system.